In Vitro Metabolism of Artepillin C by Rat and Human Liver Microsomes - Carrão, Daniel Blascke; de Albuquerque, Nayara Cristina Perez; Marques, Lucas Maciel Mauriz; Crotti, Antônio Eduardo Miller; Pilon, Alan Cesar; Bolzani, Vanderlan Da Silva; Berretta, Andresa Aparecida; de Oliveira, Anderson Rodrigo Moraes (Planta Medica, 2017)
Artepillin C, a natural product present in the Brazilian green propolis, has several biological properties. Among these properties, the antitumor action of this product is noteworthy and makes it a promising drug candidate for the treatment of several types of cancer. This paper describes the in vitro metabolism of Artepillin C in rat and human liver microsomes. The rat model suggested a sigmoidal profile for the metabolism, adapted to the Hillʼs kinetic model. The enzymatic kinetic parameters were as follows: maximal velocity = 0.757 ± 0.021 µmol/mg protein/min, Hill coefficient = 10.90 ± 2.80, and substrate concentration at which half-maximal velocity of a Hill enzyme is achieved = 33.35 ± 0.55 µM. Based on these results, the calculated in vitro intrinsic clearance for Artepillin C was 16.63 ± 1.52 µL/min/mg protein. The in vitro metabolism assay conducted on the human model did not fit any enzymatic kinetic model. Two novel metabolites were formed in both mammal microsomal models and their chemical structures were elucidated for the first time. The main human cytochrome P450 isoforms involved in Artepillin C metabolism had been identified, and the results suggest a majority contribution of CYP2E1 and CYP2C9 in the formation of the two metabolites.
Keywords: Artepillin C; enzymatic kinetics; liver microsomes; natural product; in vitro metabolism